The role of defects in solid state dewetting of ultrathin Ag film on Si(557). (15th March 2021) - Chaika, A.N.; Bozhko, S.I.; Ionov, A.M.; Sveklo, I.; Postnova, E. Yu.; Semenov, V.N.; Bisht, A.; Rabkin, E.
Abstract: We have studied the solid state dewetting of ten monolayers thick Ag film deposited on periodically patterned Si(557) surface. The annealing of the system in the ultra-high vacuum at the temperatures between 300 and 400 °C resulted in full agglomeration of the film and formation of faceted single crystalline Ag nanoparticles exhibiting bimodal size distribution. We demonstrated that some particles contain screw dislocations producing a step on the upper particle facet. We related the bimodality in particles distribution with the ability of dislocation-containing Ag particles to evolve by Ostwald ripening mechanism. Graphical abstract: Image, graphical abstract